Intranasal exposure to uranium results in direct transfer to the brain along olfactory nerve bundles. Issue 4 (June 2014) - Ibanez, Chrystelle; Suhard, David; Tessier, Christine; Delissen, Olivia; Lestaevel, Philippe; Dublineau, Isabelle; Gourmelon, Patrick
<x xml:space="preserve">Abstract</x> Aims Uranium olfactory uptake after intranasal exposure raises some concerns for people potentially exposed to airborne radionuclide contamination as the brain could be a direct target for these contaminants. A model of nasal instillation was used to elucidate the transport mechanisms of uranium to the brain and to map its localization. Methods Increasing concentrations of depleted uranium containing solutions were instilled in the nasal cavity of adult male rats. Uranium concentrations were measured using inductively coupled plasma‐mass spectrometry (ICP‐MS) 4 h after instillation. Olfactory neuroepithelium cytoarchitecture was studied using immunohistochemistry experiments. Secondary ion mass spectrometry (SIMS) microscopy was performed to localize uranium in the olfactory system. Results ICP‐MS analyses showed a frontal accumulation of uranium in the olfactory bulbs associated with a smaller increase in more caudal brain regions (frontal cortex, hippocampus and cerebellum). Uranium concentrations in the olfactory bulbs do not reach a saturation point. Olfactory nerve bundle integrity is not affected by uranium as revealed by immunohistochemistry. SIMS microscopy allowed us to show that uranium localization is mainly restricted to the olfactory neuroepithelium and around olfactory nerve bundles. It is subsequently detected in the olfactory nerve layer of the olfactory bulb. Discussion These results suggest the existence of a transcellular passage from the mucosa to the perineural space around axon bundles. Uranium bypasses the blood brain barrier and is conveyed to the brain via the cerebrospinal fluid along the olfactory nerve. Future studies might need to integrate this new contamination route to assess uranium neurotoxicity after nasal exposure.